2004
DOI: 10.1111/j.1442-200x.2004.01885.x
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative scoring in children under treatment for atopic dermatitis

Abstract: Use of well-constructed scoring forms should improve clinical assessment of patient course and treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A recent systematic review on the validation of AD outcome measures identified 16 different AD severity scales . Five of the most commonly used include Scoring Atopic Dermatitis (SCORAD), Eczema Area and Severity Index (EASI), Six Areas, Six Sites Atopic Dermatitis (SASSAD), Three Item Severity index (TIS) and the Patient‐Oriented Eczema Measure (POEM) .…”
mentioning
confidence: 99%
“…A recent systematic review on the validation of AD outcome measures identified 16 different AD severity scales . Five of the most commonly used include Scoring Atopic Dermatitis (SCORAD), Eczema Area and Severity Index (EASI), Six Areas, Six Sites Atopic Dermatitis (SASSAD), Three Item Severity index (TIS) and the Patient‐Oriented Eczema Measure (POEM) .…”
mentioning
confidence: 99%
“…Associations with allergic and non-allergic comorbidities are being increasingly reported in moderate to severe AD. Murao et al 30 have suggested that the severity of AD should be measured by adding scores based on complications of each patient. Similarly, the Singapore Guideline recommends that AD patients with psychological dysfunction should be treated as severe AD 28 .…”
Section: Discussionmentioning
confidence: 99%